Чисельне дослідження процесів перемішування в’язкої рідини у напівкрузі методом R-функцій - Шабратко, Є. Ю. (ХНУРЕ, 2021)
The problem of calculating the stationary flow of a viscous incompressible fluid in a circular region is considered. For its numerical analysis it was pro-posed to use the R-function method and the Galerkin method for non-stationary problems. The results of a computational experiment for a test problem are given.
Keywords: процес перемішування в’язкої рідини; метод R-функцій